Hybrid silicon nanocone–polymer solar cells based on a transparent top electrode. Issue 53 (11th June 2015) - Kou, Yanlei; Liu, Kong; Wang, Zhijie; Chi, Dan; Lu, Shudi; Yue, Shizhong; Li, Yanpei; Qu, Shengchun; Wang, Zhanguo
<x xml:space="preserve">Abstract</x> We utilize fully covered thin layer of transparent MoO3/Ag/ZnS as the top electrode for Si nanocone/PEDOT:PSS hybrid solar cells. By adjusting the geometrical parameters systematically, the optimized PCE was realized as 5.12%.